The Effectiveness of Canva's Interactive Media-Assisted Discovery Learning on Social Sciences Learning Outcomes Viewed from the Critical Thinking Skills - Habibah, Kurnia; Widianto , Idam Ragil; Supianto, Supianto; Christy Suryandari, Kartika (International Journal of Elementary Education, 2025)
Students' critical thinking skills and low social studies learning outcomes are caused by the lack of effective use of learning models and media. This study aims to analyze the influence of Canva's interactive media-assisted Discovery Learning model on the learning outcomes of IPAS students in grade IV elementary school reviewed from critical thinking skills. The research method used was an experiment with a quasi-experiment pre-post-test control group design. The research sample was taken using the cluster random sampling technique with a total of 33 students in the experimental group and 31 students in the control group. The data analysis techniques used include descriptive and inferential statistics with hypothesis testing using the Independent Samples t-test. The results showed that the average learning outcome of the experimental group was 399.24, while the control group was 374.87. The results of the hypothesis test showed a Sig. (2-tailed) value of 0.000 < 0.05 (α=0.05), which showed a significant difference in the learning outcomes of social studies between students in the experimental group and the control group. Based on these results, it can be concluded that Canva's interactive media-assisted Discovery Learning model has a significant influence on the learning outcomes of science science students in grade IV of elementary school. The implication of this research is that teachers can integrate the Discovery Learning model and Canva's interactive media in social studies learning to improve students' learning outcomes and critical thinking skills in elementary school.